Effectiveness and cost-effectiveness of Self-Help Plus (SH+) for preventing mental disorders in refugees and asylum seekers in Europe and Turkey: study protocols for two randomised controlled trials. Issue 5 (14th May 2019) - Purgato, Marianna; Carswell, Kenneth; Acarturk, Ceren; Au, Teresa; Akbai, Sena; Anttila, Minna; Baumgartner, Josef; Bailey, Della; Biondi, Massimo; Bird, Martha; Churchill, Rachel; Eskici, Sevde; et al.
Abstract : Introduction: This article describes two randomised controlled trials that will evaluate the effectiveness and cost-effectiveness of Self-Help Plus (SH+), a group self-help intervention developed by the WHO to reduce distress. In these trials SH+ is being tested as a preventative intervention to lower the incidence of mental disorders in asylum seekers and refugees with psychological distress resettled in Europe and Turkey. Methods and analysis: Two prospective, multicentre, randomised, rater-blinded, parallel-group studies will follow participants over a period of 12 months. One trial will be conducted in Europe and one in Turkey. In each trial, 600 asylum seekers and refugees screening positive on the General Health Questionnaire (≥3), but without a formal diagnosis of any mental disorders according to the Mini International Neuropsychiatric Interview, will be randomly allocated to SH+or to enhanced treatment-as-usual. The primary outcome will be a lower incidence of mental disorders at 6 month follow-up. Secondary outcomes will include the evaluation of psychological symptoms, functioning, well-being, treatment acceptability and indicators of intervention cost-effectiveness. Ethics and dissemination: The two trials received ethical clearance from the local Ethics Committees of the participating sites (seven sites), as well as from the WHO Ethics Committee. All participants will provide informed consent before screening and before study inclusion (a two-step procedure). The results of the trials will be disseminated in agreement with a dissemination plan that includes publication(s) in peer-reviewed journals and presentations at relevant national and international conferences and meetings. Trials registration numbers: NCT03571347, NCT03587896 .